AB0190 DO IT FAST! EARLY ASSESSMENT BY A RHEUMATOLOGIST INCREASES THE CHANCES OF RHEUMATOID ARTHRITIS BEING TREATED WITHIN THE "WINDOW OF OPPORTUNITY". (2nd June 2020) - Albuquerque, C.; Gomides, A. P.; Vargas-Santos, A. B.; Brenol, C.; Pereira, I.; Bonfiglioli, K.; Bertolo, M.; Guimarães, M. F.; Sauma, M.; Louzada, P.; Giorgi, R.; Radominsky, S.; et al.
Abstract : Background: The current concept of treating rheumatoid arthritis RA patients emphasizes the importance of early diagnosis and early initiation of disease-modifying drugs (DMARD) for a better prognosis of these patients. Objectives: To evaluate the impact of rheumatologic evaluation on the diagnosis of RA patients, as well as on the initiation of DMARD and on the clinical control of disease activity of these patients under real-life conditions. Methods: The REAL study included RA patients attending eleven public hospitals, from different regions of Brazil. All subjects met the ARA (1987) or ACR/EULAR (2010) RA classification criteria. Subjects were submitted to clinical interview with physical exam and review of medical records. Specialized assessment was defined as sequentially "early", when the rheumatologist was the 1 st or 2 nd consulted physician, and sequentially "late", when the rheumatologist was consulted after two or more other doctors. Welch's t, Mann-Whitney's U, chi-square and Spearman's rho tests were used to test hypotheses, at significance level of 0.05. The study was approved by local ethics committees and all participants granted informed consent. Results: 1057 RA patients were assessed; 89.4% (n=945) female; 56.5% (n=597) white; mean (SD) age of 56.9 (11.5) years; mean (SD) disease duration of 173.1 (114.5) months. Median [IQR] delay from symptoms onset to RA diagnosis and to the first DMARD both equaled 12 [6, 36] months. Only 28.7% received a DMARD within 6 months of symptoms onset, and 13.1% within 3 months. Most patients (64.6%) sought a general practitioner first, but 80.7% were finally diagnosed only upon rheumatologist consultation. For 28.8%, the rheumatologist was consulted after two or more other doctors. Early specialized assessment resulted in higher chances of receiving a DMARD within 6 months (OR 2.77; 95%CI [1.93, 3.97]) and within 3 months (OR 2.57; 95%CI [1.54, 4.27]) of RA onset. Late assessment was associated with lower chances of being in remission or low disease activity upon study inclusion (OR 0.53; 95%CI [0.39, 0.72]). Patients assessed early by the rheumatologist, compared to those assessed late, showed lower (mean [SD]) HAQ scores (0.877 [0.715] vs. 1.074 [0.857]; p<0.001) and DAS28-CRP scores (3.20 [1.32] vs. 3.45 [1.48]; p=0.02), and shorter delays to RA diagnosis (26.9 [46.7] vs. 44.6 [60.1] months; p<0.001) and to use the first DMARD (32.5 [58.5] vs. 50.6 [69.9] months; p<0.001). The delay to initiate a DMARD was strongly correlated to that of diagnosing RA (rho 0.816; p < 0.001). Conclusion: Most RA patients missed the window of opportunity to early treatment. Treatment delay strongly correlated with delay in diagnosis, which critically depended on the input from the rheumatologist. Late rheumatologist assessment was associated with lower chances of early RA treatment and with worse outcomes. Failure in direct transition from primary to specialized care was a common problem that needs to be solved. Disclosure of Interests: Cleandro Albuquerque Grant/research support from: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Consultant of: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Paid instructor for: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Speakers bureau: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Ana Paula Gomides Consultant of: Abvvie, Ana Beatriz Vargas-Santos Grant/research support from: Has received supporting for international medical events from AbbVie and Janssen, Claiton Brenol: None declared, Ivanio Pereira Grant/research support from: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Consultant of: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Paid instructor for: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Speakers bureau: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Karina Bonfiglioli Consultant of: Roche, Abbvie, Pfizer, Janssen and BMS, Manoel Bertolo Grant/research support from: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Consultant of: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Paid instructor for: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Speakers bureau: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Maria Fernanda Guimarães: None declared, Maria Sauma: None declared, Paulo Louzada Jr Grant/research support from: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Paid instructor for: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Speakers bureau: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Rina Giorgi Grant/research support from: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Consultant of: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Paid instructor for: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Speakers bureau: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Sebastião Radominsky Grant/research support from: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Consultant of: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Paid instructor for: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Speakers bureau: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Licia Mota Grant/research support from: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB., Speakers bureau: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB., Geraldo Castelar-Pinheiro Grant/research support from: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Consultant of: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Speakers bureau: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche